Dimensional Surface‐Enhanced Raman Scattering Nanostructures for MicroRNA Profiling. Issue 7 (23rd March 2021) - Li, Chen; Li, Si; Qu, Aihua; Xu, Chuanlai; Xu, Liguang; Kuang, Hua
Abstract : Surface‐enhanced Raman scattering (SERS) spectrum is an ultrasensitive quantitative tool for molecular fingerprinting and is very suitable for the analyzing and detecting trace substances, including low‐abundance miRNAs. Researchers have already investigated the effects of nanomaterial‐based SERS profiling on miRNA. As review herein, these SERS‐active nanostructures can be generally classified into 0D, 1D, 2D, and 3D nanostructures according to their distinct structure. These SERS‐active structures with differential structural dimensions exhibit differences in terms of detection performance which can be attributed to the unique nanomaterials involved and the overall design of the SERS nanostructures. In this review the authors focus on the design of SERS nanostructures in previous research, the advantages and disadvantages in miRNA profiling of the different dimensional nanostructures are analyzed, and some design principles to develop guidelines, to fabricate more effective SERS nano‐sensors with ultra‐high sensitivity and high levels accuracy are summarized, thereby promoting the practical application of miRNA profiling by SERS technology in complex life systems. Abstract : Herein, the advantages and disadvantages in miRNA profiling of four different dimensional surface‐enhanced Raman scattering (SERS) nanostructures are summarized and the practical application of miRNA profiling by SERS technology in complex life systems is suggested.